Procedural and clinical outcomes after repeat edge‐to‐edge transcatheter mitral valve repair. Issue 5 (18th January 2022) - Freixa, Xavier; Estévez‐Loureiro, Rodrigo; Pascual, Isaac; Carrasco‐Chinchilla, Fernando; Sanchis, Laura; Nombela‐Franco, Luis; Benito‐González, Tomás; Li, Pedro; Flores‐Umanzor, Eduardo; Amat‐Santos, Ignacio; Baz, Jose A.; Jiménez‐Quevedo, Pilar; et al.
Abstract: Background and Objectives: Evidence regarding redo percutaneous interventions for recurrent mitral regurgitation is scarce. We ought to evaluate procedural and clinical outcomes of repeated edge‐to‐edge transcatheter mitral valve repair (TMVR) interventions. Methods: This multicenter study collected individual data from eight high‐volume TMVR Centers in Spain. Between 2012 and 2020, all patients undergoing a second edge‐to‐edge TMVR intervention (Redo) were included in the study. Results: Among a total of 1028 procedures, 31 patients (3%) with residual MR ≥ 3 at follow‐up underwent a second procedure (Redo). Redo intervention was mainly conducted between the first and second year after the first procedure. The most common cause of MR progression was partial detachment (46.7%) followed by LV remodeling (35.5%). Procedural success was achieved in 87% of cases. After a mean follow‐up of 1.75 ± 1.54 years, all‐cause and cardiovascular mortality were 48.1% and 25%, respectively. Nearly half of the patients (48.1%) required at least one hospital admission for CHF within the follow‐up period. However, most of the patients presented symptomatic improvement as depicted by an NYHA class ≤2. Elective mitral surgery was conducted in only one patient at follow‐up due to insufficient MR reduction. Conclusions: According to our findings, redo edge‐to‐edge TMVR interventions were feasible and safe with a high procedural success rate. Clinical and echocardiographic follow‐up showed however modest long‐term results in this specific setting.